Description of Mychonastes koreanus sp. nov. (Sphaeropleales, Chlorophyceae) isolated from the Yun River, Republic of Korea - Lee, Ha-Eun; Kim, Taehee; Ki, Jang-Seu (Phytotaxa, 2025)
Green algae belong to the major photosynthetic organisms in aquatic environments. Their taxonomy has undergone dramatic revisions in recent decades, resulting in numerous new taxa. However, many small-celled spherical morphotypes have so far remained uncertain with regard to their classification. With the help of molecular phylogenetic methods, these taxa can be more clearly defined. In the present study, we isolated a freshwater green alga (SMU-GA001) from the Yun River, Republic of Korea. The species has spherical, solitary cells with a cup-shaped chloroplast without pyrenoids. The cell size ranged from 1.5 to 3.5 µm. Based on these morphological characteristics, we identified the species to be within the genus Mychonastes. The identity was confirmed by the phylogenetic analysis of 18S rRNA; however, the species differs from other Mychonastes species. The species identified here showed unique molecular features regarding the rRNA ITS2 sequence and its secondary structure, along with compensatory base changes (CBCs), in comparison to other Mychonastes species. These results revealed that our algae is a novel species within the genus Mychonastes, and thus we proposed it as Mychonastes koreanus sp. nov., named after Korea, the country where it was first discovered.